Real-world satisfaction and experience with injection and autoinjector device for ofatumumab indicated for multiple sclerosis - Amy Perrin Ross; Jacqueline Nicholas; Ming-Hui Tai; Stephen Yeung; Nazneen Fatima Shaikh; Helen Chen; Mariana Fernandes; Aaron Cortright; Kevin Hawkins (BMC Neurology)
Abstract Background To evaluate the overall satisfaction, device usability, and injection experience of MS patients self-administering ofatumumab using the Sensoready® autoinjector device in the United States (US). Methods This US-based, cross-sectional survey study included patients with MS (≥ 18 years) who self-administered ofatumumab using the Sensoready device within the previous 12 months of the survey. Eligible patients were administered a 30-item de novo questionnaire that focused on overall device satisfaction, device usability, convenience/flexibility for travel with the device, user confidence, injection experience, and time to administer the injection. Ratings were measured on Likert and numeric rating scales, with higher scores indicating positive responses. Results Overall, 105 patients with MS (disease-modifying therapy [DMT]-experienced: 65; DMT-naïve: 40) were included. The mean (standard deviation [SD]) age was 42.5 (12.2) years. The majority of patients (86.7%) expressed high satisfaction (i.e., rated either 4 [satisfied] or 5 [extremely satisfied] on a 5-point Likert scale) in study population. The overall mean (SD) satisfaction score with Sensoready device was 4.4 (0.7), with a higher device satisfaction reported in the DMT-experienced vs. DMT-naïve group (4.6 [0.66] vs. 4.1 [0.69]). A higher proportion of DMT-experienced patients reported high satisfaction scores as compared to DMT-naïve patients (90.8% vs. 80.0%). The most common reasons for high satisfaction included reasonable administration time (90.5%), overall ease of use (89.5%), a monthly dosing schedule of ofatumumab (89.5%), the time required for device preparation (86.7%), ease of device preparation (81.9%), device ergonomics (76.2%), and portability (73.3%). Regardless of prior DMT experience, the majority of patients felt confident to self-administer ofatumumab using the Sensoready device; moreover, the majority expressed their intention to continue with the Sensoready device and would recommend ofatumumab to others. Furthermore, 77.1% reported that the use of Sensoready device to self-administer ofatumumab was not found to interfere with their daily activities; patients reporting non-interference with their daily activities were higher in the DMT-experienced vs. DMT-naïve group (83.1% vs. 67.5%). Conclusions Regardless of prior DMT experience, patients with MS report high satisfaction levels and positive experiences with the use of the ofatumumab Sensoready device in real-world practice, mostly driven by reasonable administration time and ease-of-use.